Magmatizm riftov i skladčatych pojasov - Bogatikov, Oleg A. (Nauka, 1993)
Magmatism and geodynamics of the Great Caucasus -- Isotope investigations of the Ural and Kola alkaline provinces -- Evolution of mantle and basaltic magmatism of the intercontinental Baikal rift -- Aspects of the mantle processes
Abstract in engl. Sprache u.d.T.: Rift and fold belt magmatism. - Literaturangaben. - Zsfassungen in engl. Sprache